Teachers’ Social-Emotional Competence and Their Teaching Practices that Promote Students’ Social-Emotional Learning - Santiago, Jacklyn C. (Alipato, A Journal of Basic Education; Vol 14 (2023), 2024)
Teachers have a crucial role in the development of the social and emotional skills of students. However, little attention has been given to the cultivation of teachers’ own social-emotional competence (SEC). This mixed-methods study focuses on the SEC of teachers in the Philippines and how this SEC relates to their teaching practices that promote students’ social and emotional learning (SEL). Results from a cross-sectional survey administered to 102 public and private school teachers revealed a significant positive correlation between teachers’ SEC and their teaching practices that promote positive social and instructional interactions. Teachers’ knowledge of and amount of training received on SEL were found to have significant effects on both their SEC and implementation of SEL practices. Teaching experience was also determined to be significant to teachers’ implementation of social and emotional teaching practices. Findings from the analysis of qualitative data gathered from interviews with ten selected teachers corroborated the quantitative findings. The qualitative data further suggests that the COVID-19 pandemic may have presented a unique opportunity for teachers to strengthen their SEC and prioritize their students’ SEL. Implications of these results for teacher preparation programs and professional development are discussed.